Overabundance of Lactobacillus iners in the Urogenital Microbiome of a Female Patient with Urinary Tract Infection - Fitri Nadifah; Wayan Tunas Artama; Budi Setiadi Daryono; Endah Retnaningrum (Future Science, 2022)
The microbiome that inhabits the human body plays a role not only in maintaining health but also in causing diseases, such as urinary tract infections (UTIs). This occurs due to changes in the host's body and causes changes in the composition of the microbiota that make up the microbiome. This case report contains the results of 16S rRNA gene sequencing in the urine specimens of a 41-year-old female patient diagnosed with UTI. Illumina MiSeq was carried out for 16S rRNA gene sequencing in the V3-V4 hypervariable region. The 16S rRNA sequence yielded a total of 98,754 high-quality reads with 283 species and 299 operational taxonomic units (OTUs) identified. Based on the sequencing results, we found an overabundance (93%) of Lactobacillus iners as the most abundant and dominant taxa. Lactobacillus iners is one of the bacteria that is difficult to culture. However, with the 16S rNA gene sequencing technology, these bacteria can be detected along with their abundance in the structure of the urogenital microbiome. Bacterial overabundance may have occurred as a result of changes in the host ecology, resulting in UTI clinical symptoms. This result indicates that, in addition to maintaining the health of the urogenital organs, L. iners can also be the causative agent of UTI. An ecological perspective appears to be necessary to determine the composition and function of the microbiota, especially in patients with UTI. The data set has been sent via NCBI as a Sequence Read Archive (SRA).